KUALIFIKASI MANAJERIAL TEKNIS PRODUKSI TELUR PERUSAHAAN UD. FITRA ABADI, KECAMATAN LEIHITU, KABUPATEN MALUKU TENGAH - Adolf Heatubun; Michel J Matatula; Marcus Veerman; Heriyanus Jesayas (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2019)
The technical managerial ability to produce eggs from farmers and farm company managers is an indicator of how well businesses organize successful production and business activities. This study aims to determine the technical indicators of production efficiency in the laying hens company UD. Fitra Abadi. The study used a survey method, the location was selected purposively, and the study lasted 31 days in October 2018. The sample used was one cage block with 2,100 hens laying hens. The results showed the laying hens, UD. Fitra Abadi applies a technology package that is lower in capacity by mixing shop food (35%), corn feed (45%), and bran feed (20%). Egg production produced an average of 1,738 eggs per day (82.76% of 2,100 chickens) is below the best capacity of the peak egg-laying period of 95%. Technical indicators of production show the average production of eggs per kg of food 6.43 eggs, marginal production of -0.3 eggs, and elasticity of -0.047. The efficiency of the company's production becomes negative, and the company operates in a loss phase.